ENGLISH SPEAKING LEARNING PROBLEMS FACED BY THE STUDENTS AT THE FIRST YEAR OF SMP NEGERI 1 TIRTOMOYO WONOGIRI - WULANDARI, RIKA (2010)
This research is conducted to: 1) describe problems of the students of the first year of SMP Negeri 1 Tirtomoyo Wonogiri in learning to speak English; and 2) describe the solution of the student's problems in learning to speak English. The subject of this research is the first year students in SMP Negeri 1 Tirtomoyo Wonogiri. The writer uses descriptive qualitative research to find out the description concerning the English speaking learning problems faced. Data collect by observation dan library research. Analysis of the data use the descriptive qualitative technique about reducing the data, verifying the data; displaying the data, and conclussion. The result of study shows that: The Problems Faced in Teaching Learning Process to Speaking English in SMP Negeri 1 Tirtomoyo in 2009/2010 academic year are: a) Pronunciation, student has some differences with English in pronunciation. b) Vocabulary, the students lack of vocabulary, Lack of Grammatical Knowledge, Comprehension (lack of knowledge), fluency (grammar, vocabulary, pronunciation, and word-formation, and to apply them properly incommunication). The Solutions for the student's problems in learning to speak English are: pronunciation with pronunciation drill, improvement interest and their motivation the activities of the learning process; Vocabulary, the teacher has to explain clearly and related the tack; Gramatical with more in explanation; Comprehension with translate in Indonesian words (attention, background experience, language abilities; Fluency with reading aloud.